The Influence Of Financial Literacy, Digital Payment, And Interest In Using E-Commerce On Msme Income (A Case Study on MSME Traders in the Trade Sector in Surakarta City) - Desi Ambarwati; Noer Sasongko (Universitas Sains dan Teknologi Komputer, 2024)
This study aims to analyze the influence of financial literacy, digital payment, and interest in using e-commerce on the income of MSMEs in the trade sector in Surakarta City. Financial literacy reflects the ability of business owners to manage finances effectively, while digital payment and e-commerce play a crucial role in supporting transactions and digital marketing. Data were collected through questionnaires distributed to 115 respondents selected using purposive sampling. The results of multiple linear regression analysis indicate that financial literacy, digital payment, and interest in using e-commerce have a significant positive effect on MSME income. These findings highlight the importance of improving financial literacy and adopting digital technology as strategies to enhance MSME performance and income.